The Relationship between Grammatical and Lexical Aspects: a Study on the Compositional Theory - Mousa Ghonchepour; Zohre Ahmadypour Anari (مطالعات زبان‌‌ها و گویش‌های غرب ایران, 2022)
This article studies the relationship between grammatical and lexical aspects based on the compositional theory. The data of this study was collected from written and spoken contemporary Persian. The data indicates no one-to-one correspondence between grammatical and lexical aspects. The unbound action events are atelic while the bound ones have telic/ atelic features. The mismatch between grammatical and lexical aspects of state propositions is based on perfect or progressive interpretation of grammatical aspect and atelic feature of lexical aspect. The normal stative happenings have perfect/ progressive grammatical and atelic lexical aspects while the achievement state sentences have telic aspects. There is no one-to-one correspondence between perfect and telic aspects as well as progressive and atelic aspects in accomplishment propositions. The perfect grammatical aspects of accomplishment propositions have telic features. The durative accomplishment events show approaching to the endpoint. The grammatical aspects have an influence on lexical aspects in these events. Perfect grammatical aspects of scalar accomplishment events possess telic/ atelic lexical aspects. The lexical aspect of events is not predictable and it is not determined through inherent features of verbs, but all constituents have an effect on specifying it.